Spesolimab for generalized pustular psoriasis: a review of two key clinical trials supporting initial US regulatory approval - Gwillim, Eran C.; Nichols, Anna J. (Frontiers in Immunology, 2024)
Abnormal signaling of the interleukin-36 (IL-36) pathway appears to have a central role in generalized pustular psoriasis (GPP) immunopathology, and provides a rational therapeutic target. Spesolimab is a first-in-class humanized monoclonal antibody that binds specifically to the IL-36 receptor, and antagonizes IL-36 signaling. Spesolimab obtained regulatory approval in the United States (US) in September 2022 for use in the treatment of GPP flares in adults, and was subsequently approved for GPP flare treatment in other countries across the world. Recently, regulatory approval was granted for subcutaneous dosing of spesolimab for GPP treatment when not experiencing a flare. We review data from two key clinical trials that supported the initial US regulatory approval; the phase 1 proof-of-concept trial (ClinicalTrials.gov ID, NCT02978690), and Effisayil 1 (NCT03782792), which remains the largest and only randomized clinical trial in patients experiencing GPP flares published to date. In the phase 1 proof-of-concept trial, a Generalized Pustular Psoriasis Physician Global Assessment (GPPGA) score of 0 or 1 (clear or almost clear skin) was attained in 5/7 (71%) patients by week 1 and in all 7 patients by week 4; and the mean percent improvement in the Generalized Pustular Psoriasis Area and Severity Index (GPPASI) score from baseline was 59.0% at week 1, 73.2% at week 2, and 79.8% at week 4. In Effisayil 1, a GPPGA pustulation subscore of 0 (no visible pustules) was achieved in 19/35 (54%) patients receiving spesolimab at the end of week 1, versus 1/18 (6%) receiving placebo (difference, 49 percentage points; 95% confidence interval [CI], 21 to 67; P<0.001); and a GPPGA total score of 0 or 1 was achieved by 15/35 (43%) patients in the spesolimab group, versus 2/18 (11%) patients in the placebo group (difference, 32 percentage points; 95% CI, 2 to 53; P = 0.02). Infections at week 1 were reported in 6/35 (17%) patients receiving spesolimab and in 1/18 (6%) patients receiving placebo. These data demonstrate the efficacy and safety of spesolimab in providing rapid and sustained clinical improvement for patients with GPP flares, which translates into improved quality of life, by offering a targeted therapy for GPP.